Societies in transition: multi-cultural-man and strategic public relations (PR) challenges for PR practitioners in South Africa - De Wet, Gideon (Department of Communication Science, Unierstity of the Free State, 2008)
Over the past decade a number of countries have embarked upon dramatic sociopolitical transitions. A common denominator has always been a highly divided society filled with trauma. One such country is South Africa. A short overview is provide regarding the transition from the apartheid context to the new democratic dispensation and the huge challenges that the post 1994 South Africa has to deal with, in particular in the corporate context. The South African Reconciliation Barometer's surveys have been used to provide empirical data regarding the state of the nation with reference to particular selected areas. These statistics show a deeply divided society with high levels of mistrust. The public relations practitioner needs to negotiate these contexts in their efforts to practice integrated strategic public relations. Adler's multi-cultural-man metaphor (1985) serves as meta-theoretical framework. This article explores potential conceptual challenges for strategic public relations practitioners in their challenges to manage integrated public relations and the lessons to be learned from such traumatised societies. The extrapolation is the corporate context with the focus on integrated public relations challenges for the practitioners of public relations.
Keywords: Strategic public relations practitioners; Integrated public relations; Public relations